Of light and shadow (Farrar Straus Giroux, 2023)
Of Light and Shadow is a novel about magic, mayhem, love, and betrayal—the story of a bandit and a prince who change each other in unexpected ways. When they don’t give us our birthright, we steal it. Roshan Chaya is out for justice. Abandoned by her parents at birth and adopted by the kingdom of Jwala's most notorious bandit before his brutal murder, she is now leader of the Shadow Clan, a gang of farmers-turned-bandits impoverished by the provincial governor’s atrocities and corruption. Roshan’s goal: to avenge her adoptive father and earn back rights and dignity for her people. Prince Navin has always felt like an outcast. Second in line for the throne, he has never been close to his grandmother, Queen Bhairavi of Jwala. When a night out drinking with friends leads to his capture by the infamous Shadow Clan, Navin schemes to befriend Roshan and use her as a means to escape. His ploy, however, brings Navin closer to the corruption and poverty at the heart of Roshan’s province, raising questions about its governor and Navin’s own family. To further complicate things, the closer Roshan and Navin get, the harder it becomes to fight their growing attraction. But how can they trust each other when the world as they know it starts to fall apart? Set in a magical world inspired by the badlands of 17th century India, this standalone epic fantasy novel by Tanaz Bhathena is packed with political tensions, dangerous schemes, and swoon-worthy romance that asks the age old question: can love conquer all?